REALISASI TINDAK TUTUR LANGSUNG DALAM PRAKTIK WAWANCARA TIPE LIGHT ENTERTAIMENT MAHASISWA PRODI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS NEGERI PADANG - Sakti, Tahta Lawna; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is, to describe the realization of the continuity of the educational status of Indonesian Language student speech is State University of Padang in interviews for talk show type of light entertainment. The purpose of the descriptive is to describe, describe or depict a systematic, factual, and accurate about the facts, properties, as well as the relationship of the antarfenomena investigated. This research data is a fact of learning skills in realization of the continuity and to talk show type light entertainment and speech in the transcript of the interview performance containing follow the research results directly said is there is a realization of the continuity of students ' skill in speech taped as much as 76.77%, with the imperative mood-as 6 speech imperatives with the percentage of 1.51%, other interrogative mode-interrogative as much as 234 speech with percentage 59.10%, and declarative mode-form declarative as much as 64 speech with 16.16% percentage. Based on the results of the study it can be concluded that the realization of the continuity of the educational status of Indonesian Language student speech is State University of Padang in skill type talk show taped for light entertainment is already realized, but there needs to be the addition of a form of a question in the form of ketidaklangsungan speech. Kata Kunci: Relisasi, tindak tutur langsung, Keterampilan Berwawancara, Gelar Wicara Tipe Light Entertaiment